Upper Triassic U-Pb Age from The Agua de La Zorra Formation in Paramillos area, Mendoza Precordillera - Orellano Ricchetti, Ana Paula (2022)
The Agua de la Zorra Formation (Uspallata Group) constitutes the rift infill of the Paramillos depocenter from the Cuyo basin located in the Argentine Precordillera. This unit hosts the Paramillos de Uspallata polymetallic vein-deposit. In this contribution we report a new LA-ICP- MS zircon U-Pb age of 230.2 ± 2.2 Ma (Upper Triassic) for a tuff level that belongs to the Agua de la Zorra Formation. The obtained age is consistent with the age of the volcanism in other areas of the Cuyo basin.